Changes on the rheological properties of pectin-enriched mango nectar by high intensity ultrasound. (May 2018) - Huang, Bohui; Zhao, Kaili; Zhang, Zhuo; Liu, Fengxia; Hu, Hao; Pan, Siyi
Abstract: Effects of high intensity ultrasound (US, 5–40 min) on pectin-enriched mango nectar were evaluated, with regards to its rheological properties and related factors, including microstructure, particle size, and water-soluble pectin (WSP) changes. Results showed that the rheological properties of mango nectar exhibited a complex change, with an initial increase and subsequent decrease in apparent viscosity, storage modulus G', and loss modulus G". All these changes were ultrasonic time dependent. Ultrasound treatment caused significant degradation on suspended particles in mango nectar, as evidenced by optical microscopy, and particle-size distribution. The surface mean diameter ( D [3, 2] ) was reduced to 30.7 μm from an original value of 37.6 μm after ultrasound treatment. Moreover, US further caused the molecular degradation of WSP, with Mw being reduced from 3000 to 367 kDa in mango nectar. The interaction among them during processing determined the final rheological properties. Highlights: Ultrasound caused an initial increase and then decrease on mango nectar viscosity. The two stage rheological behavior followed different mechanism. Ultrasound decreased the particle size of mango nectar. Ultrasound decreased molecular weight of water soluble pectin in mango nectar.